Catchment-scale effects of river fragmentation: A case study on restoring connectivity. (15th June 2020) - Birnie-Gauvin, Kim; Nielsen, Jan; Frandsen, Sten Bøgild; Olsen, Hans-Martin; Aarestrup, Kim
Abstract: More than two thirds of large rivers worldwide are fragmented, threatening freshwater biodiversity, river integrity, and the services that freshwater ecosystems provide for human populations around the globe. In an effort to alleviate the impacts of barriers, engineered solutions have been developed, though with somewhat underwhelming results. River restoration, especially dam removal, is viewed as the optimal option though seldom the go-to approach. In this study, we evaluated the effects of a large restoration project (pseudo dam removal) in River Kolding, Southern Jutland, Denmark, via a before-after-control-impact (BACI) approach. Using a large dataset of electrofishing data from 74 sites (including downstream unaffected sites, reconnected sites and upstream regulated sites), we found that habitat connectivity was restored successfully, with a large increase in young-of-the-year brown trout ( Salmo trutta ) at reconnected sites, reaching similar densities to downstream (non-affected) sites. We further observed a decrease in length at reconnected sites, suggesting that natural spawning and rearing habitats were successfully restored too. Highlights: We use a BACI approach to evaluate the effects of a pseudo dam removal that reconnected one of two affected tributaries. We found an immediate increase in YOY brown trout following the restoration project. Dam removal is an efficient method to restore river connectivity and habitat suitability.